1999
DOI: 10.1096/fasebj.13.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields increase cell survival by inhibiting apoptosis via modulation of Ca2+influx

Abstract: Static magnetic fields with intensities starting from 6 gauss (6x10(-4) tesla, T) were found to decrease in an intensity-dependent fashion, reaching a plateau at 6 x 10(-3) T, the extent of cell death by apoptosis induced by several agents in different human cell systems. This is not due to a change in the mode of cell death (i.e., to necrosis) or to a delay of the process itself; rather, the presence of magnetic fields allows the indefinite survival and replication of the cells hit by apoptogenic agents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
202
1
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(224 citation statements)
references
References 31 publications
13
202
1
8
Order By: Relevance
“…Is deregulation of apoptosis the mechanism through which exposure to MFs increases the risk of tumors? In a previous paper, we showed that exposure to static, magnet-generated MFs decreases the extent of apoptosis induced by different stimuli, thus increasing the survival of some types of leukocytes despite damaging treatments via MF-induced increase of capacitating Ca 2ϩ entry (21). In the present paper, we show that static 6-mT MFs modulates Ca 2ϩ fluxes in human glioblastoma primary cultures and interferes with the apoptotic pathway of these cells under apoptogenic chemical or physical stress.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Is deregulation of apoptosis the mechanism through which exposure to MFs increases the risk of tumors? In a previous paper, we showed that exposure to static, magnet-generated MFs decreases the extent of apoptosis induced by different stimuli, thus increasing the survival of some types of leukocytes despite damaging treatments via MF-induced increase of capacitating Ca 2ϩ entry (21). In the present paper, we show that static 6-mT MFs modulates Ca 2ϩ fluxes in human glioblastoma primary cultures and interferes with the apoptotic pathway of these cells under apoptogenic chemical or physical stress.…”
supporting
confidence: 53%
“…In such cells an increased Ca 2ϩ uptake from the extracellular medium might help the cells to cope against endoplasmic reticulum emptying. In our previous study (21), we also demonstrated that MFs do not rescue thymocytes from apoptosis, which, in contrast, is slightly increased in the presence of 6 mT MFs. The choice of cell system could explain in part the many conflicting results reported by different investigators who failed to detect any apoptotic effect by MFs (26).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Moreover, GSH is a key regulator in apoptosis, since cells actively extrude intracellular GSH through specific carriers and a consequent redox disequilibrium triggers the activation of Bax and cytochrome c release [32]. Previous research shows that magnetized water and high levels of GSH reduced apoptosis by interfering with the apoptotic process [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that static HMF under 5 T has little or no effect on cell growth (1,2). Depending on the cell type, different influences of HMF on apoptosis have been reported (3)(4)(5)(6). HMF may also perturb Ca 2ϩ signaling in cells, although this is also dependent on the cell type (1,6,7).…”
mentioning
confidence: 99%